Modification of Thermal Column in Kartini Reactor Using Briquettes and Powder of Coconut Shell for BNCT: Monte Carlo Simulation - Yani, Sitti; Husin, Abd. Djamil; Sudiro, Sukma Tri Adinda (Department of Physics, Universitas Negeri Padang, 2024)
This study was analyzed the distribution of thermal neutron flux and gamma ray dose rate in the Kartini rector thermal column modified by replacing graphite material with briquettes and coconut shell powder as a moderator using Monte Carlo simulation, PHITS. The particle source uses neutrons with energies of 3 MeV, 4 MeV, and 5 MeV placed in front of the thermal column. The results showed that of the four modifications, only design 2 of the thermal column with briquettes at 3 MeV energy met the IAEA standard for Boron Neutron Capture Therapy (BNCT). The thermal column material with coconut shell powder does not meet the IAEA standard. This shows that coconut shell briquettes are more effective in moderating fast neutrons than coconut shell powder because the briquettes have the characteristic of greater density, which is almost the same value as the density of graphite.